Use of grass carp (Ctenopharyngodon idella) as a biological control agent for submerged aquatic macrophytes - Silva,A.F. (2014)
This study aimed to evaluate feed preference and control efficacy of grass carp (Ctenopharyngodon idella) on the aquatic macrophytes Ceratophyllum demersum, Egeria densa and Egeria najas. An experiment was carried out at mesocosms conditions with 2,000 liters capacity and water residence time of 2.8 days. C. demersum, E. densa e E. najas biomasses were offered individually with sixty g and coupled in similar quantities of 30 g of each species, evaluated during 81 days, envolving 6 treatments. (1 - C. demersum, 2 - E. najas, 3 -E. densa, 4 - C. demersum + E. najas, 5 - C. demersum + E. densa and 6 - E. najas + E. densa). When offered individually, E. najas and C. demersum presented the same predation rate by grass carp, which was higher than E. densa predation rate. When plants were tested in pairs, the order of feed preference was C. demersum > E. najas > E. densa. E. najas and C. demersum percentage control ranged from 73 to 83%. No relation between biomass consumption and grass carp body weight gain was observed, probably due to differences in nutritional quality among macrophyte species according to fish necessities. Therefore, it is concluded that the use of grass carp is one excellent technique to control submersed macrophytes in Brazil.